2003
DOI: 10.1002/app.13277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of glass fabric/polyester composites: Effect of silicone coatings on the fabrics

Abstract: An experimental investigation was carried out to study the effect of a silicone coating on the mechanical properties of polyester/woven glass fabric composites, fabricated by resin transfer molding. E-glass woven fabrics were coated with a silicone elastomer by solution dip coating. The effect of variation of silicone amounts on the impact resistance, toughness, and mechanical properties of the composite was determined. Short beam shear tests were performed to assess the effect of coating on the adhesion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This is not surprising since the silane coating is introduced to ensure chemical bonding at the interface, whereas in the case of clean and PDMS-treated fabrics the matrix bonds to the reinforcement only through mechanical anchoring. Moreover, in the presence of the PDMS coating, apart from the bad affinity between PDMS and polyester resin, the ability of the polyester resin to penetrate through the strands of the fabric is hindered [46].…”
Section: Composites Characterization and Ilss Measurementsmentioning
confidence: 99%
“…This is not surprising since the silane coating is introduced to ensure chemical bonding at the interface, whereas in the case of clean and PDMS-treated fabrics the matrix bonds to the reinforcement only through mechanical anchoring. Moreover, in the presence of the PDMS coating, apart from the bad affinity between PDMS and polyester resin, the ability of the polyester resin to penetrate through the strands of the fabric is hindered [46].…”
Section: Composites Characterization and Ilss Measurementsmentioning
confidence: 99%
“…The fiber-matrix interface strengthening of the fiber coating has wide applications [13][14][15][16][17][18]. Zhu et al [13] found that coating the SiO 2 -rich coating on the SiC f fiber increased the fiber-matrix interfacial strength and the resulting tensile strength of the composite up to 55 and 45%, respectively.…”
Section: Fiber Surface Modificationmentioning
confidence: 99%
“…Moreover, in the presence of the PDMS coating, apart from the bad affinity between PDMS and the polyester resin, the ability of the polyester resin to penetrate through the fabric is hindered. 13,18,19 To compare dry and wet specimens, it seems that, in the case of the silane-treated composite, water absorption does not seriously affect the ILSS. It is anticipated that the chemical bonds established through the silane coating prevent moisture penetration at the interface, that is, finishes are effective against molecular water penetration by diffusion along the glass-resin interface.…”
Section: Short Beam Shear Testmentioning
confidence: 99%
“…The former is known to chemically bond to the polyester matrix, thus hindering further water absorption, whereas the others lead to the formation of composites with weak interfacial adhesion. 12 A previous study 13 found that a PDMS coating greatly enhances the impact strength when deposited on clean glass fabrics. The same behavior was also observed when polyamide coatings were alternatively applied.…”
Section: Introductionmentioning
confidence: 98%